Altered Expression of Human Mitochondrial Branched Chain Aminotransferase in Dementia with Lewy Bodies and Vascular Dementia - Ashby, Emma L. (Neurochem Res, 2016)
Cytosolic and mitochondrial human branched chain aminotransferase (hBCATc and hBCATm, respectively) play an integral role in brain glutamate metabolism. Regional increased levels of hBCATc in the CA1 and CA4 region of Alzheimer’s disease (AD) brain together with increased levels of hBCATm in frontal and temporal cortex of AD brains, suggest a role for these proteins in glutamate excitotoxicity. Glutamate toxicity is a key pathogenic feature of several neurological disorders including epilepsy associated dementia, AD, vascular dementia (VaD) and dementia with Lewy bodies (DLB). To further understand if these increases are specific to AD, the expression profiles of hBCATc and hBCATm were examined in other forms of dementia including DLB and VaD. Similar to AD, levels of hBCATm were significantly increased in the frontal and temporal cortex of VaD cases and in frontal cortex of DLB cases compared to controls, however there were no observed differences in hBCATc between groups in these areas. Moreover, multiple forms of hBCATm were observed that were particular to the disease state relative to matched controls. Real-time PCR revealed similar expression of hBCATm mRNA in frontal and temporal cortex for all cohort comparisons, whereas hBCATc mRNA expression was significantly increased in VaD cases compared to controls. Collectively our results suggest that hBCATm protein expression is significantly increased in the brains of DLB and VaD cases, similar to those reported in AD brain. These findings indicate a more global response to altered glutamate metabolism and suggest common metabolic responses that might reflect shared neurodegenerative mechanisms across several forms of dementia. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11064-016-1855-7) contains supplementary material, which is available to authorized users.